A 'Political Suspension of the Ethical': To Be Straight With You (2007) and An Evening with Psychosis (2009). (25th September 2010) - Tomlin, Liz
This article explores the tension between the 'political' and 'ethical' dimensions of contemporary verbatim practice, through an application of Slavoj Žižek's theory of the universal symptom to two productions – DV8's To Be Straight With You (2007) and Point Blank's An Evening with Psychosis (2009). The article looks in particular at the treatment of transcripts from interviewees who offer testimonies in support of the institutional discourses that are the target of each production's ideological critique. By drawing on Žižek's understanding of ethical codes that are never 'universal', but always constituted in relations of power, the article argues that the satirical and Brechtian treatment of certain verbatim testimonies through their theatrical framing and style of presentation constitutes a justifiable 'political suspension of the ethical' in each instance.